Pirólise lenta de briquetes de resíduo de açaí em reator de leito fixo - Oliveira, Paulo Renato Souza de (2021)
The use of by-products from extractive or silvicultural chains in the Amazon can strengthen the energy scenario and be associated with sustainable development. This research proposed alternatives for the final destination of açaí seeds via the adjustment of technical parameters of briquette production and optimization of pyrolysis conditions in the bio-oil yield. Briquettes were made using pressure of 15, 20 and 25 MPa and temperatures of 120, 140 and 160 °C. Subsequently, the slow pyrolysis of the briquettes took place in a fixed bed reactor at 400, 450 and 500 °C and heating rate of 5, 10 and 15 °C.min-1. The physical properties (apparent density, volumetric expansion rate and water absorption), mechanical properties (diametrical compressive strength - CS) and energy density were analyzed. For characterization of the stones in natura the proximate analysis and chemical composition was determined; and the higher, lower and useful heating value. The chemical composition of the seeds in natura showed potential for thermal resistance as biofuel, in energy generation by direct burning and conversion by thermochemical processes. The temperature had more influence on the evaluated characteristics than the pressure. The CS was higher for briquettes manufactured at 160 ºC and 15 MPa, because the lignin acts as a binder between the particles at this temperature, however, with the increase in pressure the resistance is not favored due to the limit of resistance to compaction. The absorption rate decreased with higher pressure. The temperature affected statistically only briquettes produced at 140 ºC, but the difference between the rates observed in the other temperatures was minimal. The volumetric expansion rate showed values better or close to those found in other densified biofuels in the literature. The pyrolysis kinetics of the açaí seeds was investigated using thermogravimetric analysis (TGA). Temperature up to 900 °C under nitrogen atmosphere was employed at different TA: 5, 10 and 15 °C.min-1. The activation energy (Ea) was calculated according to differential isoconversional and Friedman and Flynn-Wall-Ozawa integral methods. The averages obtained were 169.91 and 155.82 kJ.mol-1 respectively. Subsequently, slow pyrolysis of the at TA of 5, 10, and 15 °C.min-1, and T of 400, 450, and 500 °C was performed. The residence time was 60 min. The results indicated higher bio-oil yield (BY) with the increase of the heating rate associated with the temperature up to 450 °C. With the increase in temperature, an improvement in RB was observed, but with association with the heating rate of 5 ºC.min-1. Subsequently, Response Surface Methodology (RSM) was used for BY optimization. The fit of the quadratic polynomial equation was satisfactory, due to the coefficients of determination and test for lack of fit. It was found that there is no single optimum point for the conditions studied. An inflection point was observed for BY optimization. It is concluded that maximization of bio-oil yield occurs at milder temperature associated with high heating rates or at high temperature and low rates.